ANALISIS TIPE KESALAHAN BERDASARKAN TEORI NEWMAN DALAM MENYELESAIKAN SOAL CERITA PADA MATA KULIAH MATEMATIKA DISKRIT - Oktaviana, Dwi (IAIN Palangka Raya, 2017)
This research aims to analyze the students mistakes in soving math essay-tests on the discrete Mathematics using Newman error category. This descriptive research used qualitative approach. The subjects of this research are the 7th semester students of math study program of IKIP PGRI Pontianak in academic year 2016/2017. The instrument of this research was the test items analized by Newman error category and interviews. Based on the results of data analysis it can be concluded that (1) 24% of reading errors were in form of not knowing the meaning, (2) 24%Â of comprehension error is not knowing what to look for (3) 54.67% of transformation error is in form of generating function of the problem (4) 88% of error processing skill is in form of errors in the calculation and (5) 89.33% of encoding error is in form of mistakes in makingÂ final answer of the test.